2023
DOI: 10.3390/ijms24054822
|View full text |Cite
|
Sign up to set email alerts
|

Zinc: From Biological Functions to Therapeutic Potential

Abstract: The trace element zinc (Zn) displays a wide range of biological functions. Zn ions control intercellular communication and intracellular events that maintain normal physiological processes. These effects are achieved through the modulation of several Zn-dependent proteins, including transcription factors and enzymes of key cell signaling pathways, namely those involved in proliferation, apoptosis, and antioxidant defenses. Efficient homeostatic systems carefully regulate intracellular Zn concentrations. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 148 publications
0
20
0
1
Order By: Relevance
“…During the process of wound healing, the release of Zn and P stimulates the formation of epithelial cells, which has biological functions [ 56 , 57 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the process of wound healing, the release of Zn and P stimulates the formation of epithelial cells, which has biological functions [ 56 , 57 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al also found that pycnogenol can repair hydroxyl radical-induced DNA breaks, reducing cell death and brain dysfunction [ 96 ]. Zinc can reduce the activation of NF-κB and its target gene, and increase the gene expression of A20 and PPAR-α [ 97 ], delay the oxidation process and maintain the working memory ability [ 98 ]. In addition, activated vitamin D can promote the expression of Klotho gene [ 99 ], regulate the formation of related cellular signaling systems by antioxidants [ 100 ], block the uptake of active oxygen by brain neurons, and reduce neurotoxic reactions [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors control cellular intestinal villus proliferation, differentiation, and migration through enzymes such as epidermal growth factor ( Fukada et al., 2011 ; Miguel et al., 2016 ) and insulin-like growth factor ( Freake et al., 2001 ; Sun et al., 2015 ). Zinc acts in this process as a cofactor in DNA replication and cell division enzymes, as well as DNA and RNA polymerases ( Costa et al., 2023 ). Additionally, Zn influences the maintenance of tight junction integrity, intestinal permeability, and the absorptive surface area ( Wan and Zhang, 2022 ).…”
Section: Discussionmentioning
confidence: 99%